Prevention and management of vascular complications in middle ear and cochlear implant surgery - Di Lella, Filippo; Falcioni, Maurizio; Piccinini, Silvia; Iaccarino, Ilaria; Bacciu, Andrea; Pasanisi, Enrico; Cerasti, Davide; Vincenti, Vincenzo (European archives of oto-rhino-laryngology, 2017)
The objective of this study is to illustrate prevention strategies and management of vascular complications from the jugular bulb (JB) and internal carotid artery (ICA) during middle ear surgery or cochlear implantation. The study design is retrospective case series. The setting is tertiary referral university hospital. Patients were included if presented pre- or intraoperative evidence of high-risk anatomical anomalies of ICA or JB during middle ear or cochlear implant surgery, intraoperative vascular injury, or revision surgery after the previous iatrogenic vascular lesions. The main outcome measures are surgical outcomes and complications rate. Ten subjects were identified: three underwent cochlear implant surgery and seven underwent middle ear surgery. Among the cochlear implant patients, two presented with anomalies of the JB impeding access to the cochlear lumen and one underwent revision surgery for incorrect positioning of the array in the carotid canal. Subtotal petrosectomy was performed in all cases. Anomalies of the JB were preoperatively identified in two patients with attic and external auditory canal cholesteatoma, respectively. In a patient, a high and dehiscent JB was found during myringoplasty, while another underwent revision surgery after iatrogenic injury of the JB. A dehiscent ICA complicated middle ear effusion in one case, while in another case, a carotid aneurysm determined a cholesterol granuloma. Rupture of a pseudoaneurysm of the ICA occurred in a child during second-stage surgery and required permanent balloon occlusion without neurological complications. Knowledge of normal anatomy and its variants and preoperative imaging are the basis for prevention of vascular complications during middle ear or cochlear implant surgery.